VD_FINDINFO Jug / 2017 / 4 vom 20. April 2016 - VD Tribunal cantonal (2016)
ESCROQUERIE, SURSIS À L'EXÉCUTION DE LA PEINE, AMENDE, FIXATION DE L'AMENDE, AVOCAT D'OFFICE, DÉFENSE D'OFFICE | 106 CP, 146 al. 1 CP, 146 CP, 34 CP, 40 CP, 42 al. 1 CP, 42 al. 4 CP, 44 al. 1 CP, 47 CP